Almost Slightly $ν g$-open and Almost Slightly $ν g$-closed mappings - Srinivasa Balasubramanian (Boletim da Sociedade Paranaense de Matemática, 2019)
The aim of this paper is to introduce and study the concepts of slightly $ν g$-open, slightly $ν g$-closed, almost slightly $ν g$-open and almost slightly $ν g$-closed mappings and the interrelationship between other slightly-closed maps.